2020
DOI: 10.1017/s0959269520000046
|View full text |Cite
|
Sign up to set email alerts
|

The use of eye-tracking in experimental approaches in second language acquisition research: the primary effects of Processing Instruction in the acquisition of the French imperfect

Abstract: Despite the ample database of research findings on the benefits of Processing Instruction (PI), research thus has primarily made use of offline measures to establish how L2 learners comprehend and process sentences. Using online methodology, such as eye-tracking, allows research to more directly measure implicit knowledge. The sensitivity of these measures requires meticulous design choices to ensure validity and replicability. This study provides an overview of the linguistic and physical design consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…12Studies of learner production greatly outnumber studies of learner processing in the L2 tense-aspect literature and in instructional effect studies. One of the studies included in this review, Laval and Lowe (2020), used eye-tracking in pretest and posttest. They reported that in addition to higher comprehension and production scores (offline tasks), the learners in the processing instruction group increased the fixation duration on the verb when they were asked to determine whether a sentence was present or past, and they decreased the fixation time on other content words (an online task); that is, they knew where to look for the information they needed.…”
Section: Notesmentioning
confidence: 99%
“…12Studies of learner production greatly outnumber studies of learner processing in the L2 tense-aspect literature and in instructional effect studies. One of the studies included in this review, Laval and Lowe (2020), used eye-tracking in pretest and posttest. They reported that in addition to higher comprehension and production scores (offline tasks), the learners in the processing instruction group increased the fixation duration on the verb when they were asked to determine whether a sentence was present or past, and they decreased the fixation time on other content words (an online task); that is, they knew where to look for the information they needed.…”
Section: Notesmentioning
confidence: 99%